Bacolet Road, Tobago, B.W.I. - (:unkn) unknown (S.J. Hayward, Canada, 2010)
Description at back of card: “The road at the corner of my bungalow – Ft. George on the hill.” In this photograph, Bacolet Road winds around a corner. There is a row of coconut palms on either side of the road and a well dressed lady in a hat and dress shoes, with a heel, saunters down the middle of the road with a basket held on her head. In the background is a large, grassy mound or hill with a few buildings on its top.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Rural roads--Trinidad and Tobago; Women--Trinidad and Tobago; Country life--Trinidad and Tobago; Coconut palm--Trinidad and Tobago